The Cephenniini of China. VII. New species and new records of Cephennodes Reitter of Shaanxi, Gansu and Sichuan (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2015)
Nine new Chinese species of Cephennodes are described: C. (s. str.) intricatus sp. n. (Gansu), C. (s. str.) cryptointricatus sp. n. (Gansu), C. (s. str.) monofoveatus sp. n. (Shaanxi), C. (s. str.) pinnapes sp. n. (Sichuan), C. (s. str.) elegantissimus sp. n. (Sichuan), C. (s. str.) palpalis sp. n. (Gansu), C. (Fusionodes) corpulentus sp. n. (Sichuan), C. (Fusionodes) gutta sp. n. (Shaanxi) and C. (Fusionodes) medusa sp. n. (Sichuan). Cephennodes elegantissimus and C. palpalis are not placed in any species group within Cephennodes, while the remaining new taxa belong to the excavatus group (C. intricatus and C. cryptointricatus), the taurus group (C. monofoveatus), the inflatipes group (C. pinnapes), the graeseri group (C. gutta and C. medusa) and the newly established serratus group (C. corpulentus). Additionally, new records of previously described species are given: C. (s. str.) subcaudatus Jałoszyński (Shaanxi), C. (s. str.) parabdominalis Jałoszyński (Shaanxi) and C. (s. str.) pteroscapus Jałoszyński (Sichuan).